Pelatihan Penguasaan Kosakata Bahasa Inggris Hukum Melalui Aplikasi Quizlet Pada Mahasiswa Program Studi Hukum Universitas Merangin - Sasmita, Ruwaiza; Dahri, Muhtar; Kartika Sari, Fitri; Alfionita, Feni (Vox Populi: Jurnal Umum Pengabdian Kepada Masyarakat, 2024)
This training was conducted to address the issue of mastering legal English vocabulary through the Quizlet application for students of the law study program at Merangin University, with the aim of enhancing their active participation and mastery of legal English vocabulary. It can be concluded that the training was successfully carried out as all participants followed each session with great enthusiasm. The implementation of this community service activity went well, in an orderly manner, and according to the schedule that had been set. The activity was considered successful in achieving the objectives, as evidenced by the achievement of success indicators set by the implementation team. The participants gained new knowledge and were able to practice what had been taught.